The influence of mainstream and underground music towards social life case study: among students in Faculty of Music, UiTM Shah Alam / Abdullah Hadi - Hadi, Abdullah (2011)
Most of music students take their idol as their guidance to increase their good lifestyle during study otherwise they also can release tension with their friends after tired of doing assignment and study. Most of them realize the consequences and the bad effects if they didn't control their behaviour during study. Student's lifestyle mostly influences by what they always did or the other term is their hobby. Music was the main aim for researching student's lifestyle because it is the most obvious way they spent their life on. Basically we can see it among teenage students because of their age was the biggest of number that who's always listen to any genre of music and take it for their hobbies. There are many types of genre which the teenage students like to hear. There are likes metal, R 'n' B, pop, rock, ballad, and many more. This music actually can influence them to their lifestyle and behaviour, for the examples like music students in UiTM Shah Alam. Besides, music students have their own characteristic and they would influence other students. In this moment, those students might form their own clique. In this situation, they: might be choosing their friends who love similar music influence as theirs. The reason of this situation is because they are influenced by their music and it has become their lifestyle.